Citizens influencing public policy‐making: Resourcing as source of relational power in e‐participation platforms. (2nd July 2021) - Coelho, Taiane Ritta; Pozzebon, Marlei; Cunha, Maria Alexandra
Abstract: E‐participation platforms create spaces and opportunities for participation and collaboration between governments and citizens. This paper aims to investigate the role of power on formal e‐participation platforms and digital spaces that are controlled by the governments. Although those types of platforms have been increasing in numerous countries, they have been criticised as often leading to a lack of or decrease in citizen engagement. We propose a relational view that examines how power is related to the use of resources in practice, that is, to resourcing. To explore this issue, we examine citizens' participation on three urban mobility platforms in three major Brazilian cities. Our study makes two main contributions. First, we contribute to the literature on e‐participation by explaining how a relational view of power helps to understand the nature and consequences of citizen participation in public policy‐making. Second, we integrate the concept of resourcing as both a source and constitutive element of relational power. We propose a process‐based model of resourcing as power that opens the black box of resourcing through the identification of three distinct phases in time: resourcing IN, resourcing WITHIN and resourcing OUT .